Context representation and thought disorder in schizophrenia - Roesch-Ely, Daniela; Spitzer, Manfred; Kaiser, Stefan; Weisbrod, Matthias; Pfüller, Ute (Psychopathology, 2010)
Background: Formal thought disorder (FTD) in schizophrenia is related to a disturbance in the representation of contextual information. This study aimed to assess the extent to which the ‘context module’ is disturbed in patients with schizophrenia. The context module is needed to mediate an appropriate behavioral response. It comprises 2 cognitive functions, namely working memory and behavioral inhibition, and is linked to networks in the prefrontal cortex. We compared patients with enhanced FTD (n = 15) to ones with low levels and a control group (n = 21, respectively). We hypothesized that FTD patients would have greater degradation of the context module by presenting both working memory and inhibition deficits, while in low FTD patients mild degradation of the context module would be present with working memory deficits only. Methods: Using a within-subjects design, subjects underwent a battery of neuropsychological tests with different demands on the context module. We also divided patients according to first-episode versus chronic course. Results: Our results confirmed our predictions on FTD. However, first-episode patients showed working memory deficits more than those with several episodes. Conclusion: We conclude that the context module is more degraded in FTD patients, although our results have to be interpreted with caution because of the small sample size.